EPIC 219388192b: an inhabitant of the brown dwarf desert in the Ruprecht 147 open cluster - Nowak, Grzegorz; Gandolfi, Davide (The astronomical journal, 2017)
We report the discovery of EPIC 219388192b, a transiting brown dwarf in a 5.3 day orbit around a member star of Ruprecht 147, the oldest nearby open cluster association, which was photometrically monitored by K2 during its Campaign 7. We combine the K2 time-series data with ground-based adaptive optics imaging and high-resolution spectroscopy to rule out false positive scenarios and determine the main parameters of the system.